Biofunctional Elements Incorporated Nano/Microstructured Coatings on Titanium Implants with Enhanced Osteogenic and Antibacterial Performance. Issue 23 (2nd September 2020) - Xu, Na; Fu, Jijiang; Zhao, Lingzhou; Chu, Paul K.; Huo, Kaifu
Abstract: Bone fracture is prevalent among athletes and senior citizens and may require surgical insertion of bone implants. Titanium (Ti) and its alloys are widely used in orthopedics due to its high corrosion resistance, good biocompatibility, and modulus compatible with natural bone tissues. However, bone repair and regrowth are impeded by the insufficient intrinsic osteogenetic capability of Ti and Ti alloys and potential bacterial infection. The physicochemical properties of the materials and nano/microstructures on the implant surface are crucial for clinical success and loading with biofunctional elements such as Sr, Zn, Cu, Si, and Ag into nano/microstructured TiO2 coating has been demonstrated to enhance bone repair/regeneration and bacterial resistance of Ti implants. In this review, recent advances in biofunctional element‐incorporated nano/microstructured coatings on Ti and Ti alloy implants are described and the prospects and limitations are discussed. Abstract : Recent advances in biofunctional element‐incorporated nano/microstructured coatings on Ti and Ti alloy implants are reviewed and the prospects and limitations are discussed.